IMPLEMENTASI PEMBELAJARAN BERBASIS PORTOFOLIO PADA PEMBELAJARAN IPS DI KELAS V SDI WOOWONA 2 - Ma, Anselmus Me; Novianti, Chatarina (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This research aims to find out how portfolio-based learning is implemented in social studies learning in class V of SDI Woowona 2, Rewarangga Village, East Ende District. This research is a qualitative research. Research subjects were class V students and class V teachers at SDI Woowona 2. Data collection techniques used observation, interviews and documentation methods. Data analysis techniques include data reduction, data display (data presentation), and conclusion drawing/verification (drawing conclusions). Meanwhile, checking the validity of the data was carried out using triangulation techniques, namely source triangulation and technical triangulation. The results of the research show that the implementation of portfolio-based learning in social studies learning in class V SDI Woowona 2 uses the method of creating an active student learning atmosphere, participatory learning, cooperative learning groups, reactive learning and fun learning. The obstacles faced in implementing portfolio-based learning in social studies learning in class V SDI Woowona 2 are that the use of time in portfolio-based learning in social studies learning takes a long time, costs money to create work, teachers are not diligent and patient in assessing students' work, teachers have not able to provide students with an understanding of the importance of responsibility.